Is the fee-for-service model for remuneration of medical practitioners in private practice morally justifiable? - Green, Gregory (My University, 2015)
In this research report I defend the thesis that the fee-for-service remuneration model for private medical practitioners is not morally justifiable as it does not promote a paying patient’s best interests. A review of the salary, capitation, pay-for-performance and fee-for-service payment models is followed by a review of the philosophical fundamentals of caring for patients and promoting their best interests. The suitability of the fee-for-service model as it is applied to private practice is analysed with respect to its compliance / non-compliance with these fundamentals. Particular reference is given to principlism, consequentialism and virtue ethics as well as the South African health care environment. In the absence of specific and viable alternatives I propose how a moral checklist could be applied to payment models generally in order to safeguard promotion of a patient’s best interests.
Submitted in partial fulfillment of the degree of MSc (Med) in Bioethics and Health Law Steve Biko Centre for Bioethics, University of the Witwatersrand Johannesburg, 10 April 2015